Fatigue life calculation procedure for the rotor of an embedded magnet traction motor taking into account thermomechanical loads. (October 2018) - Sikanen, Eerik; Nerg, Janne; Heikkinen, Janne E.; Gerami Tehrani, Mohammad; Sopanen, Jussi
Highlights: Realistic electric motor loss model based on measured performance data. Transient thermal model including speed dependent losses and cooling effect. Combined thermal-mechanical stress calculation Fatigue life calculation of electric vehicle traction motor. Comparison of simulated and measured temperature profiles. Abstract: Working cycle and load fluctuation have to be considered in the design process of traction motors in order to be able to optimize the size, life cycle, and performance of the electric drive. The total stress and fatigue life of an electric motor rotor are determined to a large extent by centrifugal forces, tangential forces caused by torque, and the temperature gradient along the rotor. Rapid increase in heat as a result of sudden variation in the electric current and the differing thermomechanical characteristics of the components leads to non-uniform stress in the assembly. By applying the principle of superposition to the transient mechanical and thermal stress, a multidisciplinary method is proposed for the calculation the equivalent von Mises stress for a fatigue life analysis. This paper presents a fatigue life calculation procedure considering the mechanical and thermal stresses. The method is presented using the rotor of the Electric RaceAbout (ERA) traction motor as a case example. The presented approach is validated by comparing simulated and measured temperature data from ERA drive tests at the Nürburgring Nordschleife track. The results indicate the great importance of taking into consideration both mechanical and thermal loads in lifetime calculation.